Sonic echoes - Mhishi, L; Balatbat-Helbock, L; Kloeckner, L; Chiweshe, S; M'Bala, E; Nyiha, C (KW Institute for Contemporary Art, 2022)
Curated by Lennon Mhishi, Lynhan Balatbat-Helbock, and Laura Kloeckner, Sonic Echoes is a mash-up, remix, and jam session responding to sound archives and sonicities incarcerated in colonial containments, intended to invoke and unleash their fire. Rather than recuperating cohesive sound lineages or legacies, we want to create practices of refusing genre to understand the intersections of these archived sonicities. How do they communicate with other museum “subjects”? Do they stay in tune? How can they regain sonic life? We want to explore collective and intuitive methods of critical archiving to unwind and break free from perpetuating fossilized violence. We are honored to host Zimbabwe’s queen of Mbira music Stella Chiweshe, Cameroonian sound artist, musician, and performer Elsa M’bala, and UK based Kenyan sound artist and electronic musician Charles Nyiha. Interweaving sonic fragments with conversational elements, this jam session shall will critically engage, remix, and perform the archive and stimulate sonic waves to transcend and refuse containments, walls, and borders.